Nursing theory a circle of knowledge - Moccia, Patricia; Benner, Patricia E.; National League for Nursing (New York : The League, 1987)
This video introduces a number of innovators of nursing theory--Patricia Benner, Virginia Henderson, Dorothea Orem, Martha Rogers, Callista Roy, and Jean Watson -- who explore how theory and practice are interrelated and how practice influences the development of theory
Writer/host, Patricia Moccia ; interviewees, Patricia Benner, et al.
Keywords: Nursing Theory